Transcriptomic and epigenomic analyses revealed that polycomb repressive complex 2 regulates not only developmental but also stress responsive metabolism in Brassica rapa - Nugroho, Adji Baskoro Dwi; Kim, Sujeong; Lee, Sang Woo; Kim, Dong-Hwan (Frontiers in Plant Science, 2023)
Polycomb group proteins (PcG) play a crucial role in developmental programs in eukaryotic organisms, including plants. PcG-mediated gene repression is achieved by epigenetic histone modification on target chromatins. Loss of PcG components leads to severe developmental defects. CURLY LEAF (CLF), a PcG component in Arabidopsis, catalyzes the trimethylation of histone H3 on lysine 27 (H3K27me3), a repressive histone mark in numerous genes in Arabidopsis. In this study, we isolated a single homolog of Arabidopsis CLF, namely, BrCLF, in Brassica rapa ssp. trilocularis. Transcriptomic analysis revealed that BrCLF participated in B. rapa developmental processes, such as seed dormancy, leaf and flower organ development, and floral transition. BrCLF was also involved in stress signaling and stress-responsive metabolism, such as aliphatic and indolic glucosinolate metabolism in B. rapa. Epigenome analysis showed that H3K27me3 was substantially enriched in genes related to these developmental and stress-responsive processes. Thus, this study provided a basis for elucidating the molecular mechanism of the PcG-mediated regulation of development and stress responses in B. rapa.